1994
DOI: 10.1083/jcb.127.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Signal-mediated retrieval of a membrane protein from the Golgi to the ER in yeast.

Abstract: Abstract. The Saccharomyces cerevisiae Wbpl protein is an endoplasmic reticulum (ER), type I transmembrane protein which contains a cytoplasmic dilysine (KKXX) motif. This motif has previously been shown to direct Golgi-to-ER retrieval of type I membrane proteins in mammalian cells (Jackson, M. R., T. Nilsson, and P. A. Peterson. 1993. J. Cell Biol. 121: 317-333). To analyze the role of this motif in yeast, we constructed a SUC2-WBP1 chimera consisting of the coding sequence for the normally secreted glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
247
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(259 citation statements)
references
References 70 publications
11
247
0
1
Order By: Relevance
“…These fractions were analyzed by immunoblotting with several antibodies. Previous studies have shown that ER and vacuolar membranes distribute mainly in the P13 fraction, whereas Golgi membranes are recovered in both P13 and P100 fractions (Nakano et al, 1988;Nishikawa and Nakano, 1991;Gaynor et al, 1994). In this experiment, Secl2p (ER marker) and Pho8p (vacuolar marker) were mostly detected in the P13 fraction as expected.…”
Section: Rerm Encodes a Hydrophobic Proteinsupporting
confidence: 85%
See 3 more Smart Citations
“…These fractions were analyzed by immunoblotting with several antibodies. Previous studies have shown that ER and vacuolar membranes distribute mainly in the P13 fraction, whereas Golgi membranes are recovered in both P13 and P100 fractions (Nakano et al, 1988;Nishikawa and Nakano, 1991;Gaynor et al, 1994). In this experiment, Secl2p (ER marker) and Pho8p (vacuolar marker) were mostly detected in the P13 fraction as expected.…”
Section: Rerm Encodes a Hydrophobic Proteinsupporting
confidence: 85%
“…We refer to lighter (0.2 M sorbitol/1.2 M sucrose interface) and denser (1.2 M/1.5 M sucrose interface) bands as band 1 and band 2, respectively ( Figure 13A). Consistent with the report by Gaynor et al (1994), ER cells) were separated on an SDS gel and subjected to immunoblotting using an anti-BiP antibody.…”
Section: Rerm Encodes a Hydrophobic Proteinmentioning
confidence: 60%
See 2 more Smart Citations
“…For subcellular fractionation studies, spheroplasts were labeled and processed as described (4,44). After clearing extracts of unbroken cells, lysates were centrifuged at 100000 ×g for 1 h to yield P100 particulate (membrane) and S100 soluble (cytosolic) fractions.…”
Section: Strainsmentioning
confidence: 99%